2004
DOI: 10.4049/jimmunol.172.2.1186
|View full text |Cite
|
Sign up to set email alerts
|

The Dendritic Cell Receptor DC-SIGN Discriminates among Species and Life Cycle Forms of Leishmania

Abstract: Infection of dendritic cells by the human protozoal parasite Leishmania is part of its survival strategy. The dendritic cell receptors for Leishmania have not been established and might differ in their interactions among Leishmania species and infective stages. We present evidence that the surface C-type lectin DC-SIGN (CD 209) is a receptor for promastigote and amastigote infective stages from both visceral (Leishmania infantum) and New World cutaneous (Leishmania pifanoi) Leishmania species, but not for Leis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 40 publications
4
51
0
1
Order By: Relevance
“…Dedicated receptors for microbe Ags have been characterized on macrophages and DC. TLRs and DC-specific ICAM-grabbing nonintegrin have been shown to play crucial roles in modulating the innate responses to microorganisms (40,41) and to discriminate among Leishmania species (42). To date, very few data have indicated a direct recognition by lymphocytes of parasite Ags through these specific receptors, except for the recently reported reactivity of Leishmania lipophosphoglycan with TLR2 expressed on NK cells (43).…”
Section: Discussionmentioning
confidence: 99%
“…Dedicated receptors for microbe Ags have been characterized on macrophages and DC. TLRs and DC-specific ICAM-grabbing nonintegrin have been shown to play crucial roles in modulating the innate responses to microorganisms (40,41) and to discriminate among Leishmania species (42). To date, very few data have indicated a direct recognition by lymphocytes of parasite Ags through these specific receptors, except for the recently reported reactivity of Leishmania lipophosphoglycan with TLR2 expressed on NK cells (43).…”
Section: Discussionmentioning
confidence: 99%
“…are a recurrent theme and are known to be further modulated by life cycle stage [33] and parasite species [34]. For example, the receptor DC-SIGN on human DC recognizes L. infantum and L. pifanoi but not L. major [34].…”
Section: Discussionmentioning
confidence: 99%
“…Colmenares et al (2002) identified the C-type lectin, ICAM-3-grabbing nonintegrin (DC-SIGN) as the putative receptor on dendritic cells for L. pifanoi and L. infantum amastigotes. These molecules are parasite species-restricted since another C-type lectin; L-SIGN was shown to be a receptor for L. infantum and not L. pifanoi (Colmenares et al, 2004). Internalization of particles by these C-type lectins does not result in activation of dendritic cells.…”
Section: Parasite Entry Mechanismsmentioning
confidence: 99%